Polypyrimidine tract binding proteins PTBP1 and PTBP2 associate with distinct proteins and have distinct post-translational modifications in neuronal nuclear extract - Michael E. Sullivan; Jacob A. Edberg; Christopher I. Nunez; Herbert L. Axelrod; Niroshika M. Keppetipola (PLoS ONE, 2025)
RNA binding proteins play an important role in regulating alternative pre-mRNA splicing and in turn cellular gene expression. Polypyrimidine tract binding proteins, PTBP1 and PTBP2, are paralogous RNA binding proteins that play a critical role in the process of neuronal differentiation and maturation; changes in the concentration of PTB proteins during neuronal development direct splicing changes in many transcripts that code for proteins critical for neuronal differentiation. PTBP1 can compensate for the loss of PTBP2 in some developmental contexts but not others signifying the paralogs have distinct functions. How two highly structurally similar proteins regulate different sets of neuronal exons is unclear and if known, will reveal how gene families evolved to achieve tissue-specific splicing and in turn, gene expression patterns. Here, we incubated PTBP1 and PTBP2 under splicing reaction conditions containing neuronal WERI retinoblastoma nuclear extract and probed for interacting partner proteins and chemical modifications via mass spectrometry. Our results reveal key differences in the kinds of proteins and processes the paralogs associate with under these conditions. Our data also highlight the presence of novel and distinct chemical modifications on the paralogs when incubated with neuronal nuclear extracts. Collectively, our study suggests a role for chemical modifications in regulating PTBP function in neuronal vs non-neuronal cells.